Spot Urine Albumin to Creatinine Ratio versus Urine Protein to Creatinine Ratio for the Diagnosis of Proteinuria in Pregnancy - Paroon Sanoonrat; Nattinee Srisantiroj; Marut Yanaranop (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives: To evaluate the correlation of the spot urine albumin to creatinine ratio (UACR) and the urine protein to creatinine ratio (UPCR) with 24-hour urine protein (UP-24) collection and to explore the diagnostic performances of these parameters for detecting significant proteinuria in pregnancyMaterials and Methods: This cross-sectional study was conducted on pregnant women at gestational ages 20-41 weeks who had clinically suspected proteinuria and were prospectively enrolled from November 2015 to April 2016. Random urine samples for UACR, UPCR and 24-hour urine collection for protein and creatinine were examined. Results: A total of 115 pregnant women were evaluated. Using UP-24 as the reference standard, significant proteinuria was identified in 39 cases (33.9%). UACR had a higher level of correlation than UPCR with UP-24 (r = 0.884 and 0.834, respectively). The areas under the receiver characteristics curves (ROC-AUC) of UACR and UPCR were 96.6% (95%CI; 93.8-99.9) and 94.5% (95%CI; 90.4-98.6), respectively. The diagnostic threshold of UACR for significant proteinuria was 42 mg/g. (94.9% sensitivity and 86.8% specificity), whereas the UPCR cutoff value was 0.26, (87.2% sensitivity and 90.8% specificity). Predicted UP-24 using spot UACR adjusted by maternal age had the highest ROC-AUC of 97.4% (95%CI; 95.1-99.6), with a sensitivity of 94.9% and a specificity of 90.8%.Conclusion: Spot UACR showed better correlation with UP-24 than UPCR. Spot UACR adjusted for maternal age, yielded a good diagnostic performance that was not associated with the time of urine collection and underlying diseases.